6×2-15x=0

Factor 3x out of 6×2.

3x(2x)-15x=0

Factor 3x out of -15x.

3x(2x)+3x(-5)=0

Factor 3x out of 3x(2x)+3x(-5).

3x(2x-5)=0

3x(2x-5)=0

Divide each term in 3x(2x-5)=0 by 3.

3x(2x-5)3=03

Simplify 3x(2x-5)3.

Simplify terms.

Cancel the common factor of 3.

Cancel the common factor.

3x(2x-5)3=03

Divide x(2x-5) by 1.

x(2x-5)=03

x(2x-5)=03

Apply the distributive property.

x(2x)+x⋅-5=03

Reorder.

Rewrite using the commutative property of multiplication.

2x⋅x+x⋅-5=03

Move -5 to the left of x.

2x⋅x-5⋅x=03

2x⋅x-5⋅x=03

2x⋅x-5⋅x=03

Multiply x by x by adding the exponents.

Move x.

2(x⋅x)-5⋅x=03

Multiply x by x.

2×2-5⋅x=03

2×2-5x=03

2×2-5x=03

Divide 0 by 3.

2×2-5x=0

2×2-5x=0

Factor x out of 2×2.

x(2x)-5x=0

Factor x out of -5x.

x(2x)+x⋅-5=0

Factor x out of x(2x)+x⋅-5.

x(2x-5)=0

x(2x-5)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x=0

2x-5=0

Set the first factor equal to 0.

x=0

Set the next factor equal to 0.

2x-5=0

Add 5 to both sides of the equation.

2x=5

Divide each term by 2 and simplify.

Divide each term in 2x=5 by 2.

2×2=52

Cancel the common factor of 2.

Cancel the common factor.

2×2=52

Divide x by 1.

x=52

x=52

x=52

x=52

The final solution is all the values that make x(2x-5)=0 true.

x=0,52

Solve Using the Square Root Property 6x^2-15x=0